Deaths of teenagers in car crashes: a child death review. Issue 4 (6th August 2015) - Jones, Sarah J; Heatman, Beverley
Abstract : MVCs are a leading cause of death and disability for teenagers. In Wales, a child death review process has been established to carry out thematic reviews of deaths; this approach is believed to highlight opportunities for prevention that individual case review could not. Cases were 13-year-old to 17-year-old Welsh residents who died as car drivers or passengers between 1 January 2006 and 31 December 2010. An expert panel was convened to review these cases. 28 MVCs occurred and 34 13–17 year olds died; 24 males, 10 females. 51 vehicles were involved; 23 driven by 17-year-old to 19-year-old males. 19 of the 28 MVCs occurred between 21:00 and 05:00. The risk factors identified were consistent with global research on MVC deaths and injuries to teenagers. However, there is a lack of effective interventions to tackle these in the UK. It is recommended that the implementation of Graduated Driver Licensing is considered.